The role of relief, perceived control, and prospective intolerance of uncertainty in excessive avoidance in uncertain-threat environments - Cobos-Cano, Pedro Luis; Quintero Felipe, María José; Ruiz-Fuentes, María; Vervliet, Bram; López-González, Francisco Javier (Elsevier, 2022)
Excessive avoidance is a key feature of pathological anxiety. However, the precise mechanisms underlying the development of excessive avoidance are still unknown. In the present study, we tested the hypothesis that excessive avoidance, especially in individuals with high Intolerance of Uncertainty (IU) is aimed at distress reduction via the enhancement of subjective perceived control in uncertain-threat environments. In our experiment, participants learned to avoid an uncertain aversive sound through a discriminated free operant procedure. In a later test phase in extinction, we manipulated the amount of avoidance responses available per trial by creating a limited and an unrestricted response condition. Nonetheless, the aversive sound could be effectively avoided in both conditions. We measured response frequency, avoidance confidence ratings and anxiety-predisposing traits such as intolerance of uncertainty, trait anxiety and distress tolerance. The degree of distress suffered during trials was inferred from post-trial relief ratings that were requested after trials in which the aversive sound had been omitted. In the avoidance acquisition phase, we found a positive association between prospective intolerance of uncertainty (P-IU) and the decline rate of distress. This relationship was not significant, however, when inhibitory intolerance of uncertainty (I-IU) was controlled for. At test, we found that the increase in avoidance responses led to distress reduction through the enhancement of avoidance confidence. Finally, we found a significant modulating role of P-IU in the effect of response limit on distress reduction that lends further support to our hypothesis. Specifically, P-IU was positively associated with the effect of response limit on distress. However, such modulating role was not significant when controlling for trait anxiety or I-IU.
Keywords: Incertidumbre; Intolerance of uncertainty; Prospective intolerance of uncertainty; Relief ratings; Excessive avoidance; Perceived control; Uncertain threats